The bridesman a novel - Librekhṭ, Savyon 1948- (Europa Editions, 2023)
Micha, an Israeli expat in Los Angeles working as a ghostwriter, receives an unexpected invitation. Adella, married to his beloved uncle, has bought him a ticket to Israel and booked a boutique hotel, so that he can return home and meet with her. Years before, Micha was the bridesman at Adella's wedding. He remembers her as a rebellious young woman, and orphan and an outsider, who was mocked by his close-knit family of Persian Jews. Micha is stunned by the Adella of today-poised, confident, with nothing of the uneasy woman he remembers from the past. When finally Adella reveals the true story of her life, powerful memories resurface in Micha, although nothing can prepare him for the surprise she has in store for him ...
Keywords: Families / Israel / Fiction; Family secrets / Israel / Fiction; Life change events / Fiction; Married people / Fiction; Interpersonal relations / Fiction; Jews / Fiction; Familles / Israël / Romans, nouvelles, etc; Secrets de famille / Israël / Romans, nouvelles, etc; Événements stressants de la vie / Romans, nouvelles, etc; Couples mariés / Romans, nouvelles, etc; Juifs / Romans, nouvelles, etc; FICTION / Family Life / Marriage & Divorce; Families; Family secrets; Interpersonal relations; Jews; Life change events; Married people; Israel / https://id.oclc.org/worldcat/entity/E39PBJdgWx83Xb7cjjrMXBJYyd; Domestic fiction; Fiction; Novels; Romans